HUBUNGAN STATUS PARITAS DENGAN KEJADIAN POST PARTUM BLUES DI WILAYAH KERJA PUSKESMAS JUWIRING KLATEN - Yulaikah, Siti; Susilowati, Dewi; Dewi, Diana Siska (Jurnal Kebidanan, 2024)
Postpartum blues is categorized as a mild mental disorder, therefore it is often ignored so that it is not diagnosed and not managed properly, finally it can become a difficult problem, and sometimes this disorder can develop into a more severe condition, namely depression and postpartum psychosis, which has a worse impact, especially in the problem of marital relations with husbands and the development of their children. This study aims to determine the Relationship between Parity Status and the Incidence of Postpartum Blues in the Juwiring Klaten Health Center Work Area. The design of this study is an analytical survey study. The approach used is cross-sectional. The population in this study were all postpartum mothers in the Juwiring Klaten Health Center work area as many as 44 people in March 2017. The sampling technique used purposive sampling. Data analysis used chi square. Respondent characteristics (age 20-35 years old as many as 40 people (97%), education is high school as many as 31 people (72.1%), occupation is housewife as many as 33 people (76.7%). Parity status in the work area of ​​​​Juwiring Klaten Health Center is mostly multiparous as many as 33 people (76.7%). The incidence of postpartum blues in postpartum mothers in the work area of ​​​​Juwiring Klaten Health Center is 17 people (39.5%) with moderate postpartum blues. There is a relationship between Parity Status and the Incidence of Post Partum Blues in the Work Area of ​​​​Juwiring Klaten Health Center with a p value = 0.035 (α> 0.05).